Expert system for management of urinary incontinence in women. - Gorman, R. (American Medical Informatics Association, 1995)
The purpose of this nursing informatics and outcomes research study was to determine the effectiveness of an expert system for disseminating knowledge to ambulatory women health care consumers with urinary incontinence. Clinical knowledge from the Agency for Health Care Policy and Research (AHCPR) patient guideline for urinary incontinence and research literature for behavioral treatments provided the knowledge base for the expert system. Two experimental groups (booklet and expert system) and one control group were utilized. Study results suggest the use of an expert system as one effective communication means for disseminating clinical information in an advisory capacity to ambulatory women with urinary incontinence.